FACTORS INFLUENCING WORK SATISFACTION AND COMPLIANCE OF USING PPE AMONG SHOP ASSISTANTS DURING COVID-19 - Raj k, Soumya; Pramod, Kavya; GEORGE, GODLY (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of the study was to assess the level of work satisfaction, assess compliance of using PPE among shop assistants during COVID-19 and to find the factors influencing work satisfaction. Methods: A quantitative approach with descriptive design was used for the study. Eighty samples were selected by using convenient sampling technique. The study was conducted in 4 districts of Kerala through online platform as well as through offline mediums. Results: From the study, it is evident that majority of the subjects (55%) were satisfied with their work at the time of COVID-19 and more than half (55%) of the samples have enough compliance with the use of PPE and only 7.5% have less compliance with the use of PPE. Demographic variables such age, relationship status, and work experience were found to be statically significant (p<0.05) with work satisfaction, and other variables did not have a significant association. Conclusion: This study provides a baseline for assessing the level of work satisfaction and compliance of PPE among shop assistants in selected areas. Periodic reinforcements, proper education , availability and trainings on the use of PPE can reduce the spread of Corona Virus and improve PPE compliance to an extend. Good working environment support from family and good rapport with colleagues can help to improve work satisfaction .